Advertising Management: Smes and Local Brand Development Through Brand Voice in Micro-Influencers - Muhammad, Idlofi Mahdi (Widya Cipta - Jurnal Sekretari dan Manajemen, 2024)
This research was conducted to explain and understand how packaging practices brand voice to develop SMEs and local brands to attract consumer interest. The method in this study uses a qualitative descriptive approach, namely a focused method, involving interpretation and a natural approach to the subject matter. The social settings in the research conducted are micro influencers who contribute to the development of local brands and SMEs and have carried out brand voice in promotional media. Determination of informants using purposive sampling technique. The theory applied in this study is the Advertising Management Strategy Theory which is reviewed by 2 models (AIDA Model and Securities Hierarchy Model) and supported by Brand Voice Theory which acts as a bridge in this research process. The results of this study are that the development of small businesses in product promotion involves many strategies, one of which is the use of micro influencers. These people have followers with reach that can be used to promote brands. Micro influencers can help small businesses get the attention of potential customers by creating content relevant to their industry. The steps taken by these micro influencers are clear evidence of the quantity and quality of endorsement actions on their social media which function as promotional media. Micro influencers help in increasing brand awareness by creating engaging and shareable content. Having partners helps SMEs capitalize on the trust and enthusiasm of their followers, which in turn increases brand awareness and drives sales.